EXERCISE-INDUCED ANAPHYLAXIS: CURRENT INSIGHTS FROM THE LITERATURE - Julia Borkowska; Julia Skowrońska-Borsuk; Martyna Narożniak; Adrianna Ewa Pękacka; Bartłomiej Czerwiec; Adam Borsuk; Joanna Katarzyna Pergoł; Malwina Wojtas; Zuzanna Krupa; Julia Sposób (International Journal of Innovative Technologies in Social Science, 2025)
Background: Exercise-induced anaphylaxis (EIA) is an uncommon but potentially life-threatening disorder triggered by physical activity. Its food-dependent form (FDEIA), most frequently associated with wheat and ω-5 gliadin, is the most prevalent subtype. Despite increasing recognition, both EIA and FDEIA remain underdiagnosed due to their heterogeneous presentations and multifactorial pathogenesis. Methods: A narrative literature review was conducted, focusing on publications from 2023–2025 retrieved through PubMed, Scopus, and Google Scholar. Emphasis was placed on recent clinical trials, case reports, and mechanistic studies addressing epidemiology, diagnosis, and management. Results: Recent evidence highlights the interplay between allergens, exercise, and cofactors such as nonsteroidal anti-inflammatory drugs, alcohol, and infections in lowering the threshold for reactions. While wheat and ω-5 gliadin remain the dominant triggers in FDEIA, newly described allergens, including banana, shellfish, and soy, broaden the clinical spectrum. Advances in molecular allergology, particularly component-resolved diagnostics, enhance sensitivity in identifying culprit allergens, although accessibility remains limited. Management continues to rely on trigger avoidance and the availability of self-injectable epinephrine. Promising developments include hypoallergenic wheat formulations, biologics such as omalizumab, and experimental approaches targeting mast cell signaling, notably Bruton’s tyrosine kinase inhibitors. Conclusion: EIA and FDEIA are clinically significant disorders with diverse presentations and considerable diagnostic challenges. Progress in molecular diagnostics and biologic therapies suggests a shift toward proactive, disease-modifying strategies. Future priorities include standardized diagnostic protocols, validation of emerging therapies, and enhanced clinical awareness to improve patient safety and quality of life.